Making Reforms Work in the Caribbean : A Collective Action Approach to Growth - Gallina, Andrea (World Bank, Washington, DC, 2014)
The Caribbean Growth Forum (CGF) was thus designed to respond to these concerns: to be both a forum of dialogue to identify needed reforms, and a catalyst for the implemen¬tation of agreed reform priorities, creating the needed accelerators to make reforms happen, while keeping in mind the political economy factors that have impeded reforms in the past. Since inception, the CGF process has been solidly grounded on few core principles: (i) tailor¬ing: the approach is based on locally defined problems and solutions (home grown); (ii) ac¬tion-orientation: prioritization and sequencing of reforms (e.g., combining gradual reforms with longer term structural changes) and their translation into clear, achievable and measur¬able targets, dashboards and roadmaps for implementation; (iii) transparency: making both targets and the process public to increase participation and shared commitments, thus creat¬ing a routine culture of public reporting to track progress openly (introduce behavioral chang¬es); (iv) flexibility: to ensure that the process allows for adjustments if targets are not reached and to create space for innovation; and (v) accountability: infusing a sense of shared re¬sponsibility across the coalition that is supporting change, thus moving from a blaming cul¬ture to a culture of finding solutions by doing; and, eventually, anchoring the process around a small group of responsible government officials and support them in delivering policies.